Educational attainment and cognitive behavioral therapy treatment outcome in late-life depression: a secondary analysis of a randomized controlled trial - Gerhards, Sina Kathrin; Luppa, Melanie; Zülke, Andrea; Pabst, Alexander; Claus, Mandy; Bewernick, Bettina; Elsaeßer, Moritz; Zehender, Nadine; Wagner, Michael; Peters, Oliver Hubertus; Frölich, Lutz; Schramm, Elisabeth; et al. (Journal of affective disorders, 2025)
Aim - The aim of this study is to investigate the association of different levels of educational attainment with the impact of Cognitive Behavioral Therapy for Late-Life Depression (LLD-CBT) compared to a supportive unspecific intervention (SUI). - Methods - A secondary analysis of the multicenter, randomized controlled trial “CBTlate” was conducted with n = 229 participants aged 60 years and older with moderate to severe depression who received either LLD-CBT (n = 115) or SUI (n = 114). Depressive symptoms as outcome were assessed with the 30-item Geriatric Depression Scale (GDS). Educational attainment was categorized according to the school and vocational education based system (CASMIN). Intention-to-treat analysis was performed using multilevel mixed effects linear models. - Results - While the model showed no significant overall effect of education on treatment outcome, analysis revealed a significant treatment effect for the low educational attainment group (group*time interaction, x2(2) = 6.45, p = .040) with LLD-CBT being superior to SUI in the reduction of depressive symptoms from baseline to the end of treatment (Estimated Marginal Mean Difference (EMMD) = −5.30, 95 %-CI = −8.93 to −2.12) and to follow-up (EMMD = -7.34, 95 %-CI = −11.24 to −3.43). There was no corresponding significant effect for the medium and high educational group. In the low remission and response rates were significantly higher in the LLD-CBT compared to the SUI group at follow-up. - Conclusion - Participants may have responded differently to LLD-CBT and SUI depending on their previous school and vocational education. This may be taken into account for future research and potentially when treating patients with LLD and individualizing interventions for this patient group.